Dysfunctional representation of expected value is associated with reinforcement‐based decision‐making deficits in adolescents with conduct problems. (8th April 2016) - White, Stuart F.; Tyler, Patrick M.; Erway, Anna K.; Botkin, Mary L.; Kolli, Venkata; Meffert, Harma; Pope, Kayla; Blair, James R.
Abstract : Background: Previous work has shown that patients with conduct problems (CP) show impairments in reinforcement‐based decision‐making. However, studies with patients have not previously demonstrated any relationships between impairment in any of the neurocomputations underpinning reinforcement‐based decision‐making and specific symptom sets [e.g. level of CP and/or callous‐unemotional (CU) traits]. Methods: Seventy‐two youths [20 female, mean age = 13.81 ( SD  = 2.14), mean IQ = 102.34 ( SD  = 10.99)] from a residential treatment program and the community completed a passive avoidance task while undergoing functional MRI. Results: Greater levels of CP were associated with poorer task performance. Reduced representation of expected values (EV) when making avoidance responses within bilateral anterior insula cortex/inferior frontal gyrus (AIC/iFG) and striatum was associated with greater levels of CP but not CU traits. Conclusions: The current data indicate that difficulties in the use of value information to motivate decisions to avoid suboptimal choices are associated with increased levels of CP (though not severity of CU traits). Moreover, they account for the behavioral deficits observed during reinforcement‐based decision‐making in youth with CP. In short, an individual's relative failure to utilize value information within AIC/iFG to avoid bad choices is associated with elevated levels of CP.